PROGRESSION OF DISABILITY IN PD: A SYSTEMATIC REVIEW. Issue 10 (9th September 2014) - Macleod, Angus; Grieve, Kerr; Counsell, Carl
Abstract : Disability (difficulty performing activities of daily living [ADLs]) is an important and relevant clinical outcome in Parkinson's disease (PD). One aspect of disability which can be defined objectively is dependence (being dependent upon others for help with basic ADLs) and the composite outcome "dead or dependent" is a useful, dichotomous, global measure of poor outcome. We performed a systematic review of the progression of disability and dependence in PD. We sought to all include studies of idiopathic PD followed longitudinally for at least three years reporting disability, dependence or "death or dependence". Results were analysed descriptively. Of 15, 145 references identified in the search strategy, 24 studies were included. There were heterogeneous study methods, study quality and outcome reporting, which prevented meta-analysis of disability scores. In five inception cohorts(n=857), about 10–25% of patients were dependent and 15–45% were dead or dependent at 5 years; and 20–50% were dependent and 35–70% were dead or dependent at 10 years of follow-up. In non-inception cohorts dependency estimates showed marked heterogeneity. Heterogeneity in study populations, methodology and outcome reporting made synthesis of these data difficult. Further data from representative inception studies are necessary to better understand the progression of disability in PD.